PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENTUNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN LAJU REAKSI DI KELAS XI SMA NEGERI 12PEKANBARU - Akira Rahma Fitri Akira Rahma Fitri; Miharty '; Armiyus Thaib Armiyus Thaib (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:The research was conducted in Senior High School 12 Pekanbaru. This research aims to increase student achievementon the subject ofreaction rateinclassXISenior High School 12Pekanbaru. This research is a kind of experiment researchwith pretest-posttest design. The sample consists of two classeswhich were decided randomly after doing normality and homogenity test.Experimental class is a class that is applied active learning strategy Learning Tournament, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 1,78> 1,67, means that the application of active learning strategy Learning Tournament can improve student achievement on the subject of reaction rate in class XI Senior High School 12Pekanbaru where the effect of an increase is 5,53%. Keywords:Active Learning Strategy Learning Tournament, Learning Achievement, and reaction rate